Internationales Jahrbuch für philosophische Anthropologie (De Gruyter (A), 2012)
The Annals of Philosophical Anthropology document the boundaries and interdisciplinary overlap between different empirical disciplines and their anthropologies. It explores these boundary issues philosophically, seeking to illuminate the human condition. Each edition of the Annals addresses a common theme in philosophical anthropology, and includes articles on other important topics, in addition to archival materials, biographies, and reviews.